Ibrāhīm ‘Umar al-Biqā’ī: Embracing Previous Traditions Through Intertextual Interpretation - Faruq, Umar (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
This article delves into the scholarly contributions of al-Biqā’ī, a thinker whose intellectual journey unfolded amidst the turbulent backdrop of the Crusades, a period marked by intense horizontal conflicts between Muslims and Christians. Despite the charged atmosphere of polemical exchanges, al-Biqā’ī’s approach to intertextual interpretation sets him apart as a unique figure. His receptivity to Christian and Jewish traditions in his Qur’anic interpretations reflects an openness that defies the prevailing discord. This study scrutinizes al-Biqā’ī’s perspective on the status of the Gospel and the Torah within the realm of Qur’anic interpretation. Employing textual analysis, we argue that al-Biqā’ī permits references to the Gospel and the Torah as complementary sources (isti’nās) within the interpretive framework. However, he restricts their use as foundational or legal arguments (istidlāl and ihtijāj), particularly in theological or doctrinal matters. Within the theological context, al-Biqā’ī advocates against referencing the Gospel or the Torah. Nevertheless, when these references are confined to the complementary realm, such as citing historical narratives more elaborately detailed in the Gospel and Torah, they enrich insight, knowledge, and the narrative fabric of Qur’anic interpretation.